Sistem Pendukung Keputusan Pemilihan Smartphone Terbaik Menggunakan Metode Topsis - Yaumil Yuninda Bhalqis (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
Decision support system is a support system in making a decision that is considered quite important. The decision is made based on the calculation of each method used, in this case the writer uses the TOPSIS method, which is a method where the best determined alternative is determined. In this study, several criteria were determined as a comparison, in this study the criteria used were camera, RAM, battery and smartphone prices, which then performed the calculation process with the TOPSIS method. The results of this study are the best smartphone recommendations which can later be considered strong enough for users to choose a smartphone according to their needs.